2019
DOI: 10.1111/rec.12956
|View full text |Cite
|
Sign up to set email alerts
|

Spatially balanced sampling and ground‐level imagery for vegetation monitoring on reclaimed well pads

Abstract: Land reclamation associated with natural gas development has become increasingly important to mitigate land surface disturbance in western North America. Since well pads occur on sites with multiple land use and ownership, the progress and outcomes of these efforts are of interest to multiple stakeholders including industry, practitioners and consultants, regulatory agents, private landowners, and the scientific community. Reclamation success criteria often vary within, and among, government agencies and acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…This can be done on a handwritten sheet or on a digital form to aid in photo identification later. It may be beneficial to include species that are likely to be expected in the area in the inventory even if they are not observed in the field (e.g., species within reclamation seed mixes) 18 .…”
Section: Field Data Collection and Postprocessingmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be done on a handwritten sheet or on a digital form to aid in photo identification later. It may be beneficial to include species that are likely to be expected in the area in the inventory even if they are not observed in the field (e.g., species within reclamation seed mixes) 18 .…”
Section: Field Data Collection and Postprocessingmentioning
confidence: 99%
“…The height of the monopod coupled with the camera specifications will determine the ground sample distance (GSD). In this study, a 12.1-megapixel camera was used and the monopod was set at a constant 1.3 m above the ground to obtain Nadir images at ~0.3 mm GSD 18 .…”
Section: Field Data Collection and Postprocessingmentioning
confidence: 99%
See 1 more Smart Citation
“…In this instance, the group of observers could potentially look at the video together and determine errors (e.g., why observer 1 always seemed to have higher counts than others and observers 3, 6 and 7 seemed to have lower counts than others). Other studies have shown that the use of cameras recording individuals collecting insects have been useful to correct observer bias [36] and that images provide permanent records which can be reviewed by multiple observers and stakeholder groups in vegetation surveys [37]. While our study was limited to insects, the technique presented could also be used as a non-lethal sampling strategy to study behavior in other animals (e.g., monitoring migratory bird behavior at stopover grounds).…”
Section: Discussionmentioning
confidence: 99%
“…The log ratio difference and singular decomposition were combined using neighbor constraints. Finally, residual U-Net was applied to detect the changes [22,23].…”
Section: Literature Reviewmentioning
confidence: 99%